Digitalization of Local Culture Products as a Strategy to Enhance the Competitiveness of Creative Trade (The Case of Aceh Rencong) - Doni Gunawan; Annisa Qadrunnada; Soraya Lestari (Journal of Social and Policy Issues, 2026)
This study aims to analyze and develop a digitalization strategy for the local cultural product Rencong Aceh as an effort to increase competitiveness in creative trade. Rencong as a symbol of Acehnese identity has high historical, artistic, and economic value, but its development still faces challenges in modern marketing, particularly in aspects of market access, product visualization, and cultural branding. To address these needs, this study collaborated with the Informatics study program in designing and building a web-based e-commerce platform specifically designed for the marketing of Rencong Aceh products. The research method used a qualitative descriptive approach combined with user-centered design (UCD) in the system development process. Data were obtained through observations of Rencong artisans, interviews with MSMEs, and literature studies on the digitalization of culture and creative trade. The system development stages included user needs analysis, interface design, digital catalog creation, cultural storytelling feature integration, and platform functionality testing. The research results show that digitalization through e-commerce significantly increases the visibility and market access of Acehnese Rencong products. Craftsmen gain a broader marketing space, cultural documentation becomes more standardized, and consumers can understand the historical value of Rencong through an integrated digital narrative. Cross-disciplinary collaboration between Accounting, Creative Economy, and Informatics has been shown to strengthen innovation while maintaining the authenticity of cultural products. This research recommends further developments in the form of digital payment integration, product tracking features, and social media-based promotions to strengthen global marketing.